Baoyuan Jiedu Decoction Alleviates Cancer-Induced Myotube Atrophy by Regulating Mitochondrial Dynamics Through p38 MAPK/PGC-1α Signaling Pathway - Wang, Delong; Chen, Weiqiao; Bi, Qianyu; Zong, Xin; Ruan, Jiazhao; Yin, Xiangjun; Wang, Jixin; Zhang, Honghua; Ji, Xuming (Frontiers in Oncology, 2020)
Cancer cachexia is a multifactorial syndrome characterized by continuous body wasting and loss of skeletal muscle. Impaired mitochondria function is closely associated with muscle atrophy in cancer cachexia. Our previous study confirmed the effectiveness of Baoyuan Jiedu decoction (BJD) in inhibiting cancer-induced muscle atrophy in an in vivo model. However, little is known about its mechanisms in regulating mitochondria dysfunction. In this study, we evaluated the therapeutic effect and action mechanisms of BJD against atrophy both in the Lewis-conditioned medium induced C2C12 myotube atrophy model and in a BALB/c mice xenograft model using mouse colon cancer C26 cells. The mitochondrial content was tested by 10-Nonylacridine orange (NAO) staining. Expressions of related proteins and mRNAs were detected by WB and qPCR, respectively. As a result, 18 major components were identified in BJD by UHPLC-Q Exactive analysis. As shown in the in vitro results, BJD treatment prevented prominent myotube atrophy and increased the myotube diameter of C2C12 cells. Besides, BJD treatment increased mitochondrial content and ATPase activity. Furthermore, the protein and mRNA expressions that were related to mitochondrial functions and generation such as cytochrome-c oxidase IV (COXIV), Cytochrome C (Cyt C), nuclear respiratory factor 1 (NRF-1), and mitochondrial transcription factor A (TFAM) were significantly increased in BJD treatment compared to the control group. The in vivo results showed that BJD treatment prevented body weight loss and improved the gastrocnemius index in cachexia mice. Moreover, the expressions of Atrogin-1 and muscle RING-finger protein-1 (MuRF-1) were decreased by BJD treatment. Mechanically, BJD increased the expression of peroxisome proliferator-activated receptor-gamma coactivator 1 (PGC-1α), and consistently, inhibited the expression of p38 MAPK and its phosphorylation both in vivo and in vitro. Taken together, this study identified that BJD effectively relieved cancer-induced myotube atrophy and provided a potential mechanism for BJD in regulating mitochondrial dynamics through p38 MAPK/PGC-1α signaling pathway.